Biochemical indicators of coronavirus disease 2019 exacerbation and the clinical implications (2020)
Coronavirus Disease 2019 (COVID-19) has sparked a global pandemic, affecting more than 4 million people worldwide. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can cause acute lung injury (ALI) and even acute respiratory distress syndrome (ARDS); with a fatality of 7.0 %. Accumulating evidence suggested that the progression of COVID-19 is associated with lymphopenia and excessive inflammation, and a subset of severe cases might exhibit cytokine storm triggered by secondary hemophagocytic lymphohistiocytosis (sHLH). Furthermore, secondary bacterial infection may contribute to the exacerbation of COVID-19. We recommend using both IL-10 and IL-6 as the indicators of cytokine storm, and monitoring the elevation of procalcitonin (PCT) as an alert for initiating antibacterial agents. Understanding the dynamic progression of SARS-CoV-2 infection is crucial to determine an effective treatment strategy to reduce the rising mortality of this global pandemic.